Biological Functions of Succinate (a Review of Foreign Experimental Studies) - V. V. Valeev; A. L. Kovalenko; E. V. Talikova; V. A. Zaplutanov; T. Yu. Delvig-Kamenskaya (Антибиотики и Химиотерапия, 2020)
The published data on the modern concept of the biological role of succinate, an intermediate of the citric acid cycle are analysed in the review. Special interest to succinate is determined by investigations on the mitochondrial functions at different pathologies, discovery of the hypoxia-inducible factor HIF-1 and studies on the human genome, that resulted in detection of the G-protein coupled receptors, which selectively are bound with succinate. According to the published experimental data, besides participation in oxidative reactions, succinate is considered as a key contributor to physiological, metabolic and genetic processes.